Reflection marketing capabilities in enhancing the reputation of the market organization - عذيب عامر فدعوس (Journal of Economics and Administrative Sciences, 2018)
The objective of this research is to determine the impact of marketing capabilities in building the reputation of the market organization. Marketing capabilities are one of the contemporary trends that can be adopted by the organization in the implementation of all its tasks and thus it can be assisted in achieving many advantages which are the most prominent marketing reputation in the environment The research problem indicated that there is a clear failure to employ the dimensions of marketing capabilities in the organization’s reputation. The National Center for Engineering Consultancy was selected as the field of application. The questionnaire was used as a tool to obtain the research data that were prepared based on a number of ready-made measurements after being tested for honesty and consistency. The SPSS program was used as a tool, In the introduction and analysis of research data, has resulted in the statistical tools on a number of results confirmed most of the existence of correlation and impact of significant significance of marketing capabilities in the reputation of the organization market and accordingly accepted the basic assumptions and sub-included in the research, The need for the organization to identify the most important areas that highlight the marketing capabilities that can be employed in the field of marketing reputation and thus achieve their desired goals.